Polypectomy skills of gastroenterology fellows: can we improve them? - van Doorn, Sascha C.; Bastiaansen, Barbara A. J.; Thomas-Gibson, Siwan; Fockens, Paul; Dekker, Evelien (Endoscopy International Open, 2016)
Background and aims: Currently, most training programs for gastroenterology (GI) fellows lack systematic training in polypectomy. Systematic education and direct feedback with the direct observational polypectomy skills (DOPyS) method is a simple and inexpensive way to train GI fellows in practical endoscopy. Our primary aim was to evaluate whether a lecture-based training course could improve the polypectomy skills of GI fellows. As a secondary aim, the interobserver agreement among the three assessors was evaluated.Participants and methods: We invited GI fellows to record five polypectomies, after which they attended a training course consisting of three lectures on polyps and polypectomy methods given by expert endoscopists. After training, the fellows recorded five polypectomies again. All videos were blindly assessed by three expert endoscopists, who used the DOPyS method.Results: Eight GI fellows participated in this study. There was no significant difference in the median overall competency scores before and after training; before training, 25 % (10/40) of the polypectomies were scored as “pass,” compared with 37.5 % (15/40) after training (P = 0.56). The interobserver agreement among the experts was fair (intraclass correlation coefficient [ICC] 0.34, 95 % confidence interval [CI] 0.14 – 0.52).Conclusions: Our lecture-based training course did not result in an improvement in overall competency scores for the polypectomy skills of GI fellows. Besides, the overall quality of the polypectomy techniques of the fellows was considered low. To optimize polypectomy training and competency, we believe that direct feedback in the endoscopy suite and hands-on training by dedicated teachers are essential.